Clinical and immunological features of laryngeal cryptococcosis - Oliveira, Vítor Falcão de (2024)
The literature holds few descriptions on immune response findings for laryngeal cryptococcosis. Immunology has been more extensively described in cases involving the central nervous system and the lungs, although many of these studies were conducted in animal models. We aimed to analyze the clinical and immunological characteristics of three patients with laryngeal cryptococcosis. We observed a weak participation of the innate immune response, whereas adaptive immunity showed the predominance of a Th2-type response over a Th1-type response. Most cases occur in male older adults with immunosuppressive conditions, of which HIV infection was absent. Hoarseness configured the main symptom. We found a disease that was restricted to the larynx and possibly the lungs by contiguity. Patients with hoarseness and lesions in nasal endoscopy should be investigated for cryptococcosis by a biopsy of the larynx, including with negative serum cryptococcal antigen. The immunological aspects of our findings of laryngeal involvement resembled those in the most commonly affected systems.